2020
DOI: 10.1186/s12933-020-01075-8
|View full text |Cite
|
Sign up to set email alerts
|

Augmented glycaemic gap is a marker for an increased risk of post-infarct left ventricular systolic dysfunction

Abstract: Background: Left ventricular systolic dysfunction (LVSD) occurs frequently after acute ST-segment elevation myocardial infarction (STEMI). The predisposing factors and underlying mechanism of post-infarct LVSD are not fully understood. The present study mainly investigated the correlation between glycaemic gap, a novel index of stressinduced hyperglycaemia (SIH), and post-infarct LVSD. Methods: A total of 274 first STEMI patients were enrolled in this cross-sectional study. Transthoracic echocardiography was p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 39 publications
2
4
0
Order By: Relevance
“…The link between hyperglycemia and large infarct size in the context of obs-AMI is well established, and our results are in line with previously published studies [ 40 , 41 ]. In fact, several strategies have been adopted to assess the impact of admission hyperglycemia on the extent of myocardial damage, all leading toward the same conclusion [ 42 , 43 ].…”
Section: Discussionsupporting
confidence: 93%
“…The link between hyperglycemia and large infarct size in the context of obs-AMI is well established, and our results are in line with previously published studies [ 40 , 41 ]. In fact, several strategies have been adopted to assess the impact of admission hyperglycemia on the extent of myocardial damage, all leading toward the same conclusion [ 42 , 43 ].…”
Section: Discussionsupporting
confidence: 93%
“…The link between hyperglycemia and large infarct size in the context of obs-AMI is well established, and our results are in line with previously published studies 41,42 . In fact, several strategies have been adopted to assess the impact of admission hyperglycemia on the extent of myocardial damage, all leading toward the same conclusion 43,44 .…”
Section: Hyperglycemia and In Ammatory Markers In Minocasupporting
confidence: 93%
“…It has been reported that visit‑to‑visit fasting plasma glucose variability is associated subclinical left cardiac remodeling and systolic dysfunction, independently of conventional risk factors [ 54 ]. Additionally, evidence has been provided that glycemic gap, a marker of glycemic excursion that measures the magnitude of a relative glycemic rise from chronic glycaemia, was associated with a change in left ventricular ejection fraction, and a high risk of postinfarct left ventricular systolic dysfunction [ 55 ].…”
Section: Discussionmentioning
confidence: 99%